Analisis dan Perancangan Sistem Informasi Akuntansi berbasis Web (Studi Kasus CV. TJM Production) - Achmad Fani Fajar Irawan; Suprapto Suprapto; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CV. Teguh Jaya Mandiri (TJM Production) is a company engaged in the screen printing and packaging industry. Despite having 15 years of experience, the accounting process at the company still uses the manual method. The process that is still done manually includes the preparation of general journals to the preparation of financial reports. As a result of financial reports that use manual methods only use books as processing media, several times an error occurred in data processing. The accounting process tends to take longer because if the finance staff enters the wrong data, the next process will be hampered and have to map the data to the previous process. Based on the problems that have been described, it is necessary to create an information system that can support financial accounting process on CV. Teguh Jaya Mandiri (TJM Production). Where this system can be used in the finance department to make it easier to enter data on income and expenses to be presented as information. The purpose of this research is to analyze user needs, design information systems according to requirements specifications, and evaluate requirements specifications. This study uses an object-oriented approach to perform system analysis and design. Meanwhile, the evaluation of the results used the sequence matrix method and the suitability method. This research produces current and proposed business processes, system features and requirements specifications, and system interfaces and evaluation results. The results of the evaluation of the traceability matrix show that each requirement can be traced to the features and design diagrams. While the results of the conformity evaluation show that the requirements specifications are by the features of the system.